PERFORMANCE OF SOYBEANS (GLYCINE MAX L.) AS AFFECTED BY PLANTING METHODS AND FERTILIZER TYPE IN 2018 AND 2019 RAINING SEASON AT BILLIRI, GOMBE STATE NIGERIA. - Madina, Paul; Toho, J. I.; Danlingi, H. G. (FUDMA JOURNAL OF SCIENCES, 2021)
A field experiments was carried out during the rainy season of 2018 and 2019 Tal, Billiri in Gombe state, Nigeria. The aim of the experiment is to investigate the performance of soybeans as affected by planting methods and fertilizer type. The planting methods were; Drill (50kg/ha), Dibbling (Transplanted at 25 x 75cm) and Broadcast (50kg/ha). Fertilizer used were; NPK (40kgN, 80kg P, 20kg K), SSP (20kg P) NPK/SSP (Combination of NPK and SSP at 50kg N, 100kg P and 20kg K) and Control.  The treatments were laid in a randomized complete block design with three replications. The treatments were combined to have 10 plots in a block with 1 meter between the block and 0.5 meters within the plots. During the research growth characters were measured, other character like days of 50% flower, days of maturity, number of pod per plant, seeds per pod, 1000 seed weight and seed yield were also recorded. All the parameters studies have significantly (Pâ‰¤0.05) responded to the both planting methods and fertilizer effects, where dill method was observed to perform higher in both growth character and grain yield. NPK/SSP fertilizer was significant in both growth, yield related character and over-all yield. 2019 rainy season all shows significant difference (P
Keywords: Planting, Methods, Performance and Fertilizer